2017
DOI: 10.1017/s0022215117000573
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profile of laryngeal squamous cell carcinoma patients

Abstract: Serum cytokines level cannot be used as laryngeal squamous cell carcinoma markers. Progression from T1-2 to T3-4 stage is followed by decreased serum interleukin-12 levels and increased interleukin-10 levels. Nodal involvement is associated with lower serum interleukin-12 levels. In patients with early stage tumours, serum interleukin 6, 10, 12 and 13 concentrations are significantly higher in those with supraglottic vs glottic tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Our observation showing that exacerbated NOS2 expression associated with tumor necrosis (data not shown) reinforces that interpretation. Considering recent reports, we speculate that the synthesis of NO and IL-10 by tumor-infiltrating macrophages and Tregs [32, 37, 38] would constitute the ground to the inhibition of a protective Th1 response and the condition to the development of IL-10-associated LSCC's loco-regional metastases risk [36, 39]. In turn, in these conditions, coexpression of IL-6 would increase the risk of lymph node metastases by eliciting MDSCs activity and suppressing cytotoxic T-cell function [40, 41].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our observation showing that exacerbated NOS2 expression associated with tumor necrosis (data not shown) reinforces that interpretation. Considering recent reports, we speculate that the synthesis of NO and IL-10 by tumor-infiltrating macrophages and Tregs [32, 37, 38] would constitute the ground to the inhibition of a protective Th1 response and the condition to the development of IL-10-associated LSCC's loco-regional metastases risk [36, 39]. In turn, in these conditions, coexpression of IL-6 would increase the risk of lymph node metastases by eliciting MDSCs activity and suppressing cytotoxic T-cell function [40, 41].…”
Section: Discussionmentioning
confidence: 83%
“…Considering the reports describing IL-10 upregulation in LSCC and its potential role in EMT induction in cancer [32, 33], we next hypothesized that the cytokine could, in the context of EMT induction in LSCC, be of importance. As described by others, we observed that IL-10 was increased at the systemic level (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 99%
“…The levels of these factors in the aqueous humor samples were within the detection ranges of the assays, with the minimum detectable concentration being 0.64 pg/mL for VEGF, 0.37 pg/mL for PlGF, 0.03 ng/mL for DOI: 10.1159/000488494 sICAM-1, 1.2 pg/mL for MCP-1, 0.64 pg/mL for PDGF-AA, 0.29 pg/mL for IL-6, 0.14 pg/mL for IL-8, 0.14 pg/mL for IL-12(p70), and 0.12 pg/mL for IL-13. The normal mean serum levels of these cytokines were as follows: 94.6 pg/mL for VEGF, 14.0 pg/ mL for PlGF, 8.07 ng/mL for sICAM-1, 154 pg/mL for MCP-1, 1.77 ng/mL for PDGF-AA, 4.06 pg/mL for IL-6, 36.1 pg/mL for IL-8, 259 pg/mL for IL-12(p70), and 104 pg/mL for IL-13 [8][9][10][11][12]. In addition, the molecular weights were 20 kDa for VEGF, 24 kDa for PlGF, 74 kDa for sICAM-1, 11 kDa for MCP-1, 28 kDa for PDGF-AA, 23 kDa for IL-6, 11 kDa for IL-8, 75 kDa for IL-12(p70), and 15 kDa for IL-13.…”
Section: Measurement Of Cytokines and Growth Factorsmentioning
confidence: 99%
“…It was recently reported that cisplatin in vitro at lower doses enhances antigen presentation and T-cell killing (32). Panels of cytokines have been studied in other groups of patients with a malignant disease but not up to 1 year after termination of treatment (20, 22, 25, 33, 34).…”
Section: Discussionmentioning
confidence: 99%